Student Debate Club dalam Pembelajaran Sejarah - Firdaus Al Giffari; Erlina Wiyanarti (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
Argumentation skills are included in the 4C competencies (Creative, Critical Thinking, Communicative, and Collaborative). This research is the application of learning techniques by conducting the student debate club method, which can make students more active by developing speaking skills in the following lessons, especially in terms of expressing their opinions or arguments. In this study, there were three cycles in which each cycle carried out one action using the Class Action Research (CAR) model designed by Kemmis and McTaggart consisted of planning, implementing, observing, and reflecting. The choice of CAR is to be able to change and improve the quality of learning according to the planned goals. Sub indicators regarding the argumentation skills used are confident in arguing, not questioning whether or not an argument is true, voice clarity, fluent when speaking, appreciating other people’s arguments, criticizing other people’s arguments wisely, presenting arguments logically and analytically, and presenting arguments based on argumentation.